Hydration and improved properties of magnesium oxysulfate cement modified by phosphoric acid. Issue 10 (15th April 2021) - Wang, Nan; Yu, Hongfa; Bi, Wanli; Gong, Wei; Zhang, Na; Ma, Haiyan; Wu, Chengyou
Abstract : Magnesium oxysulfate (MOS) cement is often seen as a 'green engineering material in the twenty-first century'. However, low mechanical strength is one of the major drawbacks for large-scale applications of MOS cement. In this paper, MOS cement with desirable strength was prepared by adding phosphoric acid. The effects of phosphoric acid on the hydration process, hydration products and microstructure of MOS cement were studied in detail using isothermal calorimetry, X-ray diffraction, Fourier transform infrared spectrometry, mercury intrusion porosimetry and scanning electron microscopy. It was found that the incorporation of phosphoric acid could retard the hydration process and increase the setting time of MOS cement. Furthermore, the incorporation of phosphoric acid was shown to increase the compressive strength through its effect in promoting the formation of 5Mg(OH)2 ·MgSO4 ·7H2 O. The space-filling properties and directional growth characteristics of 5Mg(OH)2 ·MgSO4 ·7H2 O contributed to a more compact and uniform microstructure of the MOS cement formed.